Copper-catalyzed direct arylation of indoles and related (hetero)arenes: a ligandless and solvent-free approach - Pandey, Dilip K.; Shabade, Anand B.; Punji, Benudhar (Advanced Synthesis & Catalysis, 2020)
A ligandless and solvent-free copper-catalyzed method for the regioselective C-H bond arylation of indoles and related heteroarenes is reported. The use of CuCl efficiently catalyzes the direct coupling of diverse heteroarenes with aryl iodides via chelation-assistance. This reaction could tolerate sensitive and structurally diverse functionalities, including halides, ethers, thioethers, amines, indolyl, pyrrolyl and carbazolyl groups. The directing group, 2-pyridinyl can be smoothly removed to generate C-2 arylated free-NH indoles, and the arylated indoles can further be functionalized into Tryptamine derivatives. Preliminary mechanistic study revealed a radical pathway for the arylation reaction.
Keywords: Arylation; C-H activation; Chelation-assistance; Copper; Indole; Solvent-free

Advances in C(sp(2))-H/C(sp(2))-H oxidative coupling of (Hetero)arenes using 3d transition metal catalysts - Bansal, Sadhna; Shabade, Anand B.; Punji, Benudhar (Advanced Synthesis & Catalysis, 2021)
C-H/C-H oxidative coupling has emerged as a straightforward and powerful technique for the construction of (hetero)biaryls, with substantial application to drug discovery, agrochemicals, biology, and material sciences. Mainly aryl-aryl, aryl-heteroaryl, and heteroaryl-heteroaryl couplings via double C(sp(2))-H activation using 4d or 5d noble transition metal catalysts have been extensively studied. Considering the earth-abundant and inexpensive nature of 3d transition metals, the sustainable development of C(sp(2))-H/C(sp(2))-H oxidative coupling employing such metal catalysts has gained significant attention. In this review, we present a comprehensive overview of C(sp(2))-H/C(sp(2))-H oxidative coupling of (hetero)arenes catalyzed by 3d transition metals.
Keywords: (hetero)biaryls; 3d transition metal; Biaryls; C-H activation; cross-dehydrogenative coupling

Unactivated alkyl halides in transition-metal-catalyzed C-H bond alkylation - Ankade, Shidheshwar B.; Shabade, Anand B.; Soni, Vineeta; Punji, Benudhar (ACS Catalysis, 2021)
Alkylation represents an important organic transformation in molecular science to develop privileged alkylated arenes and heteroarenes. Especially, the direct C-H bond alkylation using unactivated alkyl halides is a straightforward and attractive approach from both the step-economy and chemoselectivity perspectives. Substantial progress has been made in the direct alkylation using primary, secondary, and tertiary alkyl halides along with the methylation and fluoroalkylation. This Review broadly summarizes the transition-metal-catalyzed alkylations of C-H bonds on various arenes and heteroarenes with unactivated alkyl halides until October 2020. On the basis of the substrates utilized for alkylation, the Review is divided into two major sections: alkylation of arenes and alkylation of heteroarenes.
Keywords: (hetero)arenes; Alkylation; C-H activation; transition metals; unactivated alkyl halides

Room temperature chemoselective hydrogenation of C=C, C=O and C=N bonds by using a well-defined mixed donor Mn(I) pincer catalyst - Shabade, Anand B.; Sharma, Dipesh M.; Bajpai, Priyam; Gonnade, Rajesh G.; Vanka, Kumar; Punji, Benudhar (Chemical Science, 2022)
Chemoselective hydrogenation of C=C, C=O and C=N bonds in alpha,beta-unsaturated ketones, aldehydes and imines is accomplished at room temperature (27 degrees C) using a well-defined Mn(I) catalyst and 5.0 bar H-2. Amongst the three mixed-donor Mn(I) complexes developed, kappa(3)-((PNNPyz)-P-R2-N-3)Mn(CO)(2)Br (R = Ph, Pr-i, Bu-t); the Bu-t -substituted complex ((PNNPyz)-P-tBu2-N-3)Mn(CO)(2)Br shows exceptional chemoselective catalytic reduction of unsaturated bonds. This hydrogenation protocol tolerates a range of highly susceptible functionalities, such as halides (-F, -Cl, -Br, and -I), alkoxy and hydroxy, including hydrogen-sensitive moieties like acetyl, nitrile, nitro, epoxide, and unconjugated alkenyl and alkynyl groups. Additionally, the disclosed method applies to indole, pyrrole, furan, thiophene, and pyridine-containing unsaturated ketones leading to the corresponding saturated ketones. The C=C bond is chemoselectively hydrogenated in alpha,beta-unsaturated ketones, while the aldehyde's C=O bond and imine's C=N bond are preferentially reduced over the C=C bond. A detailed mechanistic study highlighted the non-innocent behavior of the ligand in the ((PNNPyz)-P-tBu2-N-3) Mn(I) complex and indicated a metal-ligand cooperative catalytic pathway. The molecular hydrogen (H-2) acts as a hydride source, whereas MeOH provides a proton for hydrogenation. DFT energy calculations supported the facile progress of most catalytic steps, involving a crucial turnover-limiting H-2 activation.

Manganese-catalyzed chemoselective direct hydrogenation of α,β-epoxy ketones and α-ketoamides at room temperature - Shabade, Anand B.; Singh, Rahul K.; Gonnade, Rajesh G.; Punji, Benudhar (Advanced Synthesis & Catalysis, 2024)
Chemoselective hydrogenation of alpha,beta-epoxy ketones and alpha-ketoamides is achieved at room temperature (25 degrees C) using 2.0 bar H-2 and a pincer-ligated Mn(I) catalyst that provides synthetically valuable alpha-hydroxy epoxides and alpha-hydroxy amides. This protocol applies to a wide range of alkyl- and aryl-substituted alpha,beta-epoxy ketones, including terpenes (alpha-ionone, nootkatone, and R-carvone)- and steroids (testosterone and progesterone)-derived epoxy ketones, and tolerates H-2 sensitive functionalities, such as halides, acetyl, nitrile, nitro, epoxide, alkenyl and alkynyl groups. Additionally, alpha-ketoamides bearing reducible functional groups, including acetyl and diazo benzene, were untouched under this protocol and selectively converted to alpha-hydroxy amides. A preliminary mechanistic study highlighted the metal-ligand cooperative H-2 activation process.
Keywords: alpha; beta-epoxy ketones; chemoselectivity; direct hydrogenation; manganese; Metal-ligand cooperation